A Relação homem-natureza, a fenomenologia do cuidar e a dimensão formativa - MEDINA, Patrícia (2011)
This is a theoretical study devoted to reconstructing conceptions of nature-care-ethics theme, in an expository approach of Martin Heidegger (2002) ideas, in conversation with Hans Jonas (2004-2006), aiming, in the future, to subsidize the philosophical foundations an environmental education methodology. The research method was the phenomenological hermeneutics of Heidegger, expressed in his work Being and Time . The basis of reflection is the relationship between man and nature, its actual sense and verifying that Care (Sorge) can serve as critical to our civilization and as a guiding principle of convivial with nature. If the technique and technology take on a new sense of ethics because of the central role they now occupy, it will be able to come to a state of irreversibility for nature and human life, requiring that human behavior becomes duty subject. The ethics need will be exponentially greater as much as the powers of human action are governed by it. Only an ethics based on the human being, maintenance and custody of existence can have an effective sense. This indicates that care takes on the original centrality and provides a lumen to the merits of its value and its meaning to life that causes one diverse devise to the society. Care should constitute the root of ethics, as it has its psychological basis in the human capacity to transcend the concrete situation of the will directed to itself, to make decisions and live for the common welfare, being around its formative dimension: responsibility is the care recognized as an obligation towards other living beings when there is a threat to the vulnerability of live.